DYNAMICS OF POVERTY AND INEQUALITY AMONG CROP FARMERS IN GHANA - Torvikey, D. G.; Tsekpo, K. O.; Afram, A. (UDS International Journal of Development, 2019)
The study examined the nature of poverty and inequality in Ghana by using Ghana Living Standards Survey Six (GLSS 6) data and qualitative data collected in Kwaebibirem District of the Eastern region of the country. Poverty and inequality are niches for certain categories of people located in specific geographical locations and in certain types of employment. The study found that in rural agrarian areas, farmers, especially those who cultivate food crops are the poorest in the country.Socio-cultural factors such as land ownership structures, intra-household decision making dynamics, climatic conditions, and lack of infrastructure to support rural agriculture explain poverty as differentiated by geography, gender and crop types. We recommend that programmes that aim at reducing poverty and inequality target affected agro ecological zones, food crop farmers and women who are the populations mostly hit by poverty. Policies and programmes such as One Village One Dam (1V1D), Planting for Food and Jobs (PFJ) and One District, One Factory(1D1F) which articulate government’s aspirations for agriculture and industrial development are framed to respond to specific questions that relate to agricultural production and marketing in the country. Therefore, these programmes must focus on the social segments of the society that are the poorest in the country. Keywords: Ghana, Poverty, Inequality, Crop farmers, Gend